2023
DOI: 10.1002/jbm.a.37522
|View full text |Cite
|
Sign up to set email alerts
|

Engineering high throughput screening platforms of cervical cancer

Abstract: Cervical cancer is the second leading cause of cancer‐related death in women under 40 and is one of the few cancers to have an increased incidence rate and decreased survival rate over the last 10 years. One in five patients will have recurrent and/or distant metastatic disease and these patients face a 5‐year survival rate of less than 17%. Thus, there is a pressing need to develop new anticancer therapeutics for this underserved patient population. However, the development of new anticancer drugs remains a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 92 publications
1
27
0
Order By: Relevance
“…We developed a unique multilayer multicellular model designed to replicate the complex Specifically, the bottom hydrogel layer was developed using a blend of Col I, fibrinogen, and synthetic polymers-GelMA or PEGDA. Echoing our previous findings, 19 we found that varying Col I and fibrinogen concentrations within the range of 0.5 to 2.5 mg/mL significantly influenced microvessel formation and cancer invasion. Specifically, 1.91 mg/mL Col I and 0.6 mg/mL fibrinogen maximized microvessel length and endometrial cancer invasion, demonstrating significant interactions with each other.…”
Section: Discussionsupporting
confidence: 84%
“…We developed a unique multilayer multicellular model designed to replicate the complex Specifically, the bottom hydrogel layer was developed using a blend of Col I, fibrinogen, and synthetic polymers-GelMA or PEGDA. Echoing our previous findings, 19 we found that varying Col I and fibrinogen concentrations within the range of 0.5 to 2.5 mg/mL significantly influenced microvessel formation and cancer invasion. Specifically, 1.91 mg/mL Col I and 0.6 mg/mL fibrinogen maximized microvessel length and endometrial cancer invasion, demonstrating significant interactions with each other.…”
Section: Discussionsupporting
confidence: 84%
“…(28) However, the GelMA hydrogel has enough flexibility in its mechanical properties that allows the incorporation of more ECM components to approximate the human cervix better, a focus of future work. (20,29) We also showed that the GelMA-hydrogel model had high cell viability and promoted cell growth over 48 hours. GelMA has proven to have good transport of nutrients and oxygen that enables cell response over time.…”
Section: Discussionmentioning
confidence: 76%
“…In a prior study, we successfully demonstrated that using gelatin methacrylate (GelMA) as the main component in a 3D in vitro model allowed phenotypic cell responses that captured the histology of the tumor microenvironment. (20) Notably, GelMA at 8.7% w/v was observed to support cervical cancer progression. (20) Despite its success in modeling cervical cancer, our 3D model reflected characteristics of metastatic cancer and is therefore unsuitable for studying cervical dysplasia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have used DoE to predict responses of hydrogels and cells within hydrogels in systems with multiple input variables. 8,[11][12][13][14] This approach can be widely used in regenerative medicine applications such as scaffold design, cell culture optimization, and the development of in vitro model systems, accelerating the timeframe in which new platforms can be optimized. [15][16][17] In this study, we were specifically interested in tuning the properties of hyaluronic acid hydrogels formed via hydrazone crosslinking.…”
Section: Introductionmentioning
confidence: 99%